Trace Metal Requirements and Interactions in Symbiodinium kawagutii - Rodriguez, Irene B.; Ho, Tung-Yuan (Frontiers in Microbiology, 2018)
Photosynthetic organisms need trace metals for various biological processes and different groups of microalgae have distinctive obligate necessities due to their respective biochemical requirements and ecological niches. We have previously shown that the dinoflagellate Symbiodinium kawagutii requires high concentrations of bioavailable Fe to achieve optimum growth. Here, we further explored the trace metal requirements of S. kawagutii with intensive focus on the effect of individual metal and its interaction with other divalent metals. We found that low Zn availability significantly decreases growth rates and results in elevated intracellular Mn, Co, Ni, and Fe quotas in the dinoflagellate. The results highlight the complex interaction among trace metals in S. kawagutii and suggest either metal replacement strategy to counter low Zn availability or enhanced uptake of other metals by non-specific divalent metal transporters. In this work, we also examined the Fe requirement of S. kawagutii using continuous cultures. We validated that 500 pM of Fe was sufficient to support maximum cell density during steady state growth period either at 26 or 28ºC. This study shows that growth of S. kawagutii was limited by metal availability in the following order, Fe > Zn > Mn > Cu > Ni > Co. The fundamental information obtained for the free-living Symbiodinium shall provide insights into how trace metal availability, either from ambient seawater or hosts, affects growth and proliferation of symbiotic dinoflagellates and the interaction between symbiont and their hosts